PERSEPSI MASYARAKAT SURABAYA TENTANG IKLAN â€œMANFAAT PAJAKâ€ DI TELEVISI - Ulfa, Anita; Darmawan, Arif; Soenarjanto, Bagus (Universitas 17 Agustus 1945 Surabaya, 2015)
Perception is a stimulus that is perceived by the individual, organized and then interpreted so thatthe individual realizes and understands what is perceived. In other words perception is a process thatinvolves the entry of messages or information into the human box. Perception is called the core ofcommunication because if individual perceptions are inaccurate, then the individual is not likely tocommunicate effectively. Perceptions that determine the individual to choose a message and ignore theother message. The research with the title of perception of Surabaya society about advertisement of